2021
DOI: 10.21865/ridep59.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Cyberstalking Scale (IPCS): evidências psicométricas no Brasil

Abstract: O cyberstalking, refere-se a um padrão de comportamento repetido, intencional e indesejado direcionado às vítimas. Considerando o contexto dos relacionamentos íntimos e o papel de agressor, verifica-se um maior envolvimento desse grupo em condutas antissociais e delitivas, entretanto, tal conduta ainda é pouco explorada pela literatura. Portanto, uma medida adequada para rastrear a perpetração do cyberstalking ajudará na compreensão da temática em diferentes contextos. Em dois estudos (N=467), foram avaliados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 36 publications
3
5
0
8
Order By: Relevance
“…Higher scores indicate a higher level of the evaluated construct. In the countries of the first world, such as Australia, it showed adequate internal reliability (.92) and construct validity with the dark personality and sadism (March et al, 2022;Smoker & March, 2017), as in Brazil (da Silva et al, 2021) where it also demonstrated concurrent validity with dark personality and consistency above .70. Regarding its factorial structure, the study by March et al (2022) yielded a threedimensional structure, while that of da Silva et al (2021) found a dimensional one.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…Higher scores indicate a higher level of the evaluated construct. In the countries of the first world, such as Australia, it showed adequate internal reliability (.92) and construct validity with the dark personality and sadism (March et al, 2022;Smoker & March, 2017), as in Brazil (da Silva et al, 2021) where it also demonstrated concurrent validity with dark personality and consistency above .70. Regarding its factorial structure, the study by March et al (2022) yielded a threedimensional structure, while that of da Silva et al (2021) found a dimensional one.…”
Section: Methodsmentioning
confidence: 93%
“…Therefore, the value of the present study is to be the first in the scientific literature to evaluate the psychometric properties of the intimate partner cyberstalking scale in Spanish language: a short and self administered questionnaire with good properties. On the other hand, unlike the two previous studies (da Silva et al, 2021;March et al, 2023), this research used larger samples and a greater number of variables to examine its concurrent validity. Finally, the fact that the few existing studies detected different factorial structures also contributes to the scientific literature.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Além dessas, foram incluídas perguntas sobre o uso de redes sociais, como: quais redes sociais o participante e o parceiro usam, tempo de uso das redes sociais e perguntas sobre isolamento social no auge da pandemia em 2020, tais como: avaliação do grau em que o participante considera que se isolou socialmente, o tempo em que o participante ficou em isolamento social por conta da pandemia, resposta aberta foi disponibilizado para que o participante deixasse sua opinião ou qualquer tipo de comentário sobre a pesquisa, caso desejasse. Adicionalmente, o questionário continha os seguintes instrumentos.IES Scale for SNSs (ISS) -Interpersonal Electronic Surveillance Scale forIntimate Partner Cyberstalking Scale (IPCS): versão brasileira(Silva et al, 2021). A IPCS foi adaptada para o Brasil a partir do instrumentode Smoker e March (2017), para avaliar de maneira global os comportamentos de perpetração do cyberstalking.…”
unclassified
“…Exemplos de itens são: "Se meu (minha) parceiro (a) sair, possivelmente verificarei suas contas on-line (Facebook, Twitter, Instagram, etc) para verificar o que ele (a) está fazendo" e "Já tirei 'prints' (capturas de tela) de informações encontradas no telefone/computador do meu parceiro sem que ele (a) soubesse." No estudode Silva et al (2021) a escala apresentou coeficiente alpha de Cronbach de 0,93 e neste estudo o coeficiente alpha foi 0,89.…”
unclassified